Beyond Critique: The Partners for Change Outcome Management System as an Alternative Paradigm to Psychiatric Diagnosis. (January 2018) - Duncan, Barry L.; Sparks, Jacqueline A.; Timimi, Sami
Critics claim that current psychiatric diagnostic systems lack reliability, validity, and clinical utility; are incompatible with known evidence of how change occurs in psychotherapy; are compromised by bias; and risk harmful effects for clients. This article argues that the Partners for Change Outcome Management System (PCOMS), a transparent, egalitarian process that collects and utilizes client feedback at each session, convincingly addresses these concerns. Furthermore, it suggests that PCOMS offers a viable alternative to the reimbursement and administrative functions of the Diagnostic and Statistical Manual of Mental Disorders and the International Classification of Diseases . The authors propose that PCOMS represents a radical realignment of the practitioner/client relationship via full, dialogical partnership at every level of psychotherapy practice and thus constitutes a step toward a new paradigm that reconnects psychotherapy and humanistic psychology with its core relational values.